The Impact Of The Aukus Alliance On China's Influence In The Indo-Pacific Region - Yusup Imannurdin; Aries Sudiarso; Dohar Sianturi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
On September 15, 2021 United States President Joe Biden, British Prime Minister Boris Johnson, and Australian Prime Minister Scott Morrison agreed on a new defense pact, called AUKUS . AUKUS can be said to be a continuation of America's strategy in an effort to counteract the development of China's influence in the Indo-Pacific region which has become increasingly massive due to several Asian countries' policies, such as the Nine Dash Line, One China Policy, Belt and Road Initiative (BRI), to economic improvement and significant military annually. Previously, the US had also strengthened the Quadrilateral Security Dialogue (QUAD) cooperation up to Five Eye as an effort to counter China's developments. China, which views the defense pact as a highly irresponsible threat and an open challenge to their growing influence in the Indo-Pacific. This paper will analyze China's influence in the Indo-Pacific Region after the emergence of the formation of the AUKUS alliance . The topics were analyzed using the Regional Security Complex Theory using a qualitative descriptive method. Upon further analysis , it can be seen that there were significant differences in China's influence before and after the formation of the AUKUS alliance in the Indo-Pacific Region.